PERBEDAAN HASIL BELAJAR STATIKA ANTARA METODE CERAMAH DENGAN METODE PROBLEM POSING PADA SISWA KELAS XII TEKNIK KONSTRUKSI KAYU SMK NEGERI 1 JAKARTA - Shelly Hardiyanti; Tuti Iriani; Nira Nasution (LPPM Universitas Negeri Jakarta, 2012)
This research aims to know the significant difference of learning outcome for Static Course between presentation method and problem posing method to the students grade XII majoring in Timber Construction Subject at SMK Negeri 1 Jakarta. As the student’s learning outcome has not fulfilled the KKM for the Static course, so the problem posing method is applied to overcome the problem. Based on this method, the students are compulsory to be active in practicing for some tasks of Static which is created as self creating problems along with its solutions. The duration of the research is conducted from February 2012. The research method is experimental method. The populations are 36 students and the samples are also 36 students which is also considered using saturated sampling. It means that the number of population and sample is the same. The instrument used in this research is testing instrument (learning outcome test). The instrument consists of 10 essay problems. This instrument is valid and the reliability result among the instrument is 0.99 with a high correlation. The data is originated from the normally distributed and homogeneous population. The hypothesis is tested using t test and resulted thitung > ttabel or 2.44 > 1.697, so the H0 is rejected and the hypothesis is accepted.As the conclusion, there is a significant difference of learning outcome for Static course between presentation method and problem posing method to the students grade XII majoring in timber construction at SMK Negeri 1 Jakarta. The result of this research shows a productive learning output between the usage of Microsoft PowerPoint and Microsoft Word as the media of learning process for the subject: Vocational Furniture in SMKN 52 Jakarta. Based on that, we will conclude that the research hypothesis proposed is accepted and proved that the usage of Microsoft PowerPoint gives more effective result in learning output compared to the usage of Microsoft Word. So it is suggested for the application of the Microsoft PowerPoint as the alternative media in learning process especially for the Subject of Vocational Furniture